(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article analyzes domestic scientific research in physical culture and sports during the period of Russian aggression towards Ukraine since 2014. The State Research Institute of Physical Culture and Sports serves as the center for planning scientific research and coordinating the efforts of scientists. The main issues of professional scientific publications in Ukraine of categories "A" and "B" in the field of Physical Culture and Sports (specialty 017) are characterized, with a total of 30 publications (25 in category "B" (83.4%), 5 in category "A" (16.6%)). An overview of regulatory documents regarding the training of scientific personnel in Ukraine in the field of physical culture and sports has been conducted. Based on the analysis of abstracts of dissertations on topics related to physical culture and sports, the features and directions of scientific research have been identified. It is noted that these topics also involved work in related fields and specialties such as pedagogy, philosophy, sociology, law, management, biology, and others. The majority of defended dissertations until 2020 were in the specialty 24.00.02 "Physical Culture, Physical Education of Various Population Groups," while the least were in 24.00.03 "Physical Rehabilitation." This indicates insufficient attention to the issues of physical education for individuals with health deviations. Research in the field of Physical Culture and Sports (specialty 017) in 2020 was conducted in the following areas: athlete training, sports types, fitness and recreation, physical education of schoolchildren, students, and military personnel. Although the number of works on physical education for schoolchildren and students has decreased in recent years, more attention is being paid to health fitness and recreation. The need to improve the content of scientific research at the present stage is justified as an important prerequisite for reforming the sphere of physical culture and sports in Ukraine. The situation of war necessitates a shift in focus towards the physical training of youth, preparing them for the defense of Ukraine, and fostering their patriotic upbringing during physical education and sports activities.